PENGAMBILAN KEPUTUSAN RASIONAL DAN BOUNDED TERHADAP KINERJA PEGAWAI - Dina .; Sugeng Rusmiwari (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Human life is always filled by decision-making. Decision-making is a science and an art that must be sought, learned, owned and developed maximally to gain benefit and solutions that maximize value, in improving the performance of employees for the benefit of the organization. However, this problem is still an ecological phenomenon between rational and bounded decision making, so employees’ performance becomes the answer to the problem. This research is a quantitative research. The samples used was a purposive sampling, with the main data collection techniques with a questionnaire and supported by the documentation. The results of this study proved that rational and bounded decision making had a very positive effect on employees’ performance known by t count (2.521 and 3.624). There was a performance improvement of 66.7%. Based on these results, in improving the performance of employees required a quick and decisive decision-making process in order to play an important role to create employees’ behaviors. Based on the explanation above, it could be understood that the aspects of performance required loyalty, initiative, honesty, discipline, personality, cooperation, creativity, work result, skills and responsibilities and solutions; Completeness of facilities infrastructure, work facilities availability, and other adequate support such as telecommunications and informatics technology. Keywords: Rational Decision, Bounded, Employee Performance Abstrak: Kehidupan manusia selalu diisi oleh peristiwa pengambilan keputusan. Pengambilan keputusan, ilmu maupun seni yang harus dicari, dipelajari, dimiliki dan dikembangkan secara maksimum dalam meraih manfaat serta solusi yang memaksimalkan nilai, dalam meningkatkan kinerja pegawai untuk kepentingan organisasi. Namun, masalah ini masih fenomena ekologis antara pengambilan keputusan rasional dan bounded, sehingga kinerja pegawai menjadi jawaban atas persoalan tersebut. Penelitian ini menggunakan jenis penelitian kuantitatif. Sampel yang digunakan purposive sampling, dengan teknik pengumpulan data utama digunakan kuesioner didukung oleh dokumentasi. Hasil penelitian ini membuktikan bahwa pengambilan keputusan rasional dan bounded memiliki pengaruh yang sangat positif terhadap kinerja pegawai diketahui dengan nilai thitung (2,521 dan 3,624) terdapat peningkatan kinerja sebesar 66,7%. Berdasarkan hasil tersebut maka dalam meningkatkan kinerja pegawai dibutuhkan proses pengambilan keputusan secara cepat dan tegas sehingga berperan penting untuk menciptakan perilaku pegawai. Berdasarkan penjelasan maka dapat dipahami bahwa aspek dalam kinerja diperlukan kesetiaan, prakarsa, kejujuran, kedisiplinan, kepribadian, kerjasama, kreativitas, hasil kerja, kecakapan dan tanggungjawab serta penyelesaian; kelengkapan sarana prasarana, tersedianya sarana kerja, dan pendukung lainnya yang memadai seperti teknologi telekomunikasi dan informatika. Kata Kunci: Keputusan Rasional, Bounded, Kinerja Pegawai